2015
DOI: 10.1016/j.dnarep.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The structural basis of XRCC1-mediated DNA repair

Abstract: Scaffold proteins play a central role in DNA repair by recruiting and organizing sets of enzymes required to perform multi-step repair processes. X-ray cross complementing group 1 protein (XRCC1) forms enzyme complexes optimized for single-strand break repair, but participates in other repair pathways as well. Available structural data for XRCC1 interactions is summarized and evaluated in terms of its proposed roles in DNA repair. Mutational approaches related to the abrogation of specific XRCC1 interactions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 168 publications
(240 reference statements)
1
100
0
3
Order By: Relevance
“…Previous researches have reported that X-ray repair cross-complementing group 1 (XRCC1) is involved in the BER pathway through repairing DNA single-strand breaks, while both X-ray repair cross-complementing group 2 (XRCC2) and X-ray repair crosscomplementing group 3 (XRCC3) participate in the HRR pathway by repairing DNA doublestrand breaks [16][17][18][19]. As suggested by earlier studies, polymorphisms of these genes are related to thyroid cancer risk [6,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 94%
“…Previous researches have reported that X-ray repair cross-complementing group 1 (XRCC1) is involved in the BER pathway through repairing DNA single-strand breaks, while both X-ray repair cross-complementing group 2 (XRCC2) and X-ray repair crosscomplementing group 3 (XRCC3) participate in the HRR pathway by repairing DNA doublestrand breaks [16][17][18][19]. As suggested by earlier studies, polymorphisms of these genes are related to thyroid cancer risk [6,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 94%
“…The encoding protein of XRCC1 acts as a scafold protein in SSBR and BER pathways via the interaction with Pol β, DNA ligase III, and PARP [73]. According to data from SNP database, more than 50 GSNPs in the coding region of XRCC1 gene, which lead to amino acid substitution, have been identiied.…”
Section: The Xrcc1 Gsnps and Afb1-hcc Among Guangxiese Populationmentioning
confidence: 99%
“…The scaffold protein XRCC1 is critically involved in BER and single-strand break repair [32, 33]. To demonstrate XRCC1 contribution to repair, we used XRCC1 wild type and null heterozygote primary mouse ear fibroblasts derived from littermate animals.…”
Section: Resultsmentioning
confidence: 99%